A large-scale study of how districts' curriculum policies and practices shape teachers' mathematics lesson planning. Issue 6 (1st November 2020) - Bieda, Kristen N.; Lane, John; Evert, Kimberly; Hu, Sihua; Opperman, Amanda; Ellefson, Nicole
ABSTRACT: Early career teachers (ECTs) face unprecedented pressure to fulfill expectations of 'highly effective' teachers within their first few years of teaching. Lesson planning is an important precursor to effective instruction, yet little is known about how the social and institutional contexts where ECTs work influences their planning. In this paper, we report findings from a large-scale study of elementary ECTs' mathematics lesson planning practice to shed light upon the nature of ECTs' lesson planning and factors influencing their lesson planning practice. Informed by the conceptualization of the curriculum enactment process, we present our findings of 67 ECTs' planning practices across four school districts, with distinct profiles for each district as defined by districts' official curriculum and the instructional materials available for teachers and students to use. We found that differences in the designated curriculum in each district corresponded with differences in how groups of ECTs utilize curricular objectives and instructional materials, and how they engage with colleagues during the lesson planning process. Implications for the preparation and induction of ECTs are discussed.